Answer:
y= 7^-t
Step-by-step explanation:
Equation for exponential decay:
An equation represents exponential decay if a term between 0 and 1 is elevated to the independent variable.
In this question:
First option 4 is elevated, so not exponential decay.
Second option:
![7^{-t} = \frac{1}{7^t} = (\frac{1}{7})^{t}](https://tex.z-dn.net/?f=7%5E%7B-t%7D%20%3D%20%5Cfrac%7B1%7D%7B7%5Et%7D%20%3D%20%28%5Cfrac%7B1%7D%7B7%7D%29%5E%7Bt%7D)
, thus, the second option represents exponential decay.
Answer:
Step-by-step explanation:
((10²-8)+4)×3=288
(10²-8)+4=(100-8)+4=92+4=96
96×3=288
32.0 you just add the first and last numbers then muptily the middle number by you anwser and divdie your 2 anwsers to gether
<span>24 cans costs £6
6/24 = 0.25 each can
5 * 0.25 = </span><span>£1.25
answer: </span>£1.25 for <span>5 cans</span>